Outdoor teaching as an alternative to Emergency Remote Teaching during the COVID-19 pandemic - Tone Stuler Myhre; Jean-Marc Dewaele (Foxton Books, 2022)
The recent and still ongoing COVID-19 pandemic has highlighted the vulnerability of an education system built around in-door teaching. Worldwide, schools closed down to reduce the spread of the virus and where it was possible students and teachers were forced to switch to Emergency Remote Teaching (ERT), described as "a temporary shift of instructional delivery to an alternate delivery mode due to crisis circumstances" (Hodges et al., 2020).